Answer:
2 x + 7
Explanation:
Simplify the following:
(2 x^2 + 17 x + 35)/(x + 5)
Factor the quadratic 2 x^2 + 17 x + 35. The coefficient of x^2 is 2 and the constant term is 35. The product of 2 and 35 is 70. The factors of 70 which sum to 17 are 7 and 10. So 2 x^2 + 17 x + 35 = 2 x^2 + 10 x + 7 x + 35 = 5 (2 x + 7) + x (2 x + 7):
(5 (2 x + 7) + x (2 x + 7))/(x + 5)
Factor 2 x + 7 from 5 (2 x + 7) + x (2 x + 7):
((2 x + 7) (x + 5))/(x + 5)
((2 x + 7) (x + 5))/(x + 5) = (x + 5)/(x + 5)×(2 x + 7) = 2 x + 7:
Answer: 2 x + 7